THE ROLE OF PT GAPURA ANGKASA IN GIVING REWARDS TO CHILDREN OF ACHIEVEMENT EMPLOYEES - Ardiasa, I Putu; Putu Abiyasa, Agus (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Rewards can indirectly increase students' motivation to learn so that they can achieve good learning achievements. In the learning process, rewards also have an important meaning. Awards reinforce the positive behavior of students. Besides that, he is also able to encourage himself to take the initiative and be enthusiastic about learning. The reward itself has meaning as a skill in providing reinforcement and a positive response to the behavior of students that allows the repetition of the behavior. outstanding employees by PT Gapura Angkasa is a form of community service carried out by PT Gapura Angkasa. This action is taken to give appreciation to children so that they are always eager to learn.